The effect of mindfulness intervention on anxiety among patients with coronary heart disease prior to cardiac catheterization - Desi Rusiana Alfiani; Irna Nursanti; Wati Jumaiyah; Hayatun Naimah; Dedi Dedi (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Cardiovascular disease remains a leading global health burden, with Coronary Heart Disease (CHD) accounting for nearly half of cases. Cardiac catheterization, widely performed in Indonesia, is vital for diagnosis and treatment but often provokes significant anxiety, potentially affecting hemodynamic stability. Mindfulness-based interventions have shown effectiveness in reducing psychological distress, enhancing emotional regulation, and improving patient resilience. However, evidence on their application in Indonesian pre-catheterization patients is limited, underscoring the need for context-specific research to optimize holistic care. Purpose: To examine the effect of mindfulness intervention in reducing anxiety prior to cardiac catheterization. Method: A quasi-experimental non-equivalent control group design was employed to examine mindfulness therapy effects among coronary heart disease patients scheduled for cardiac catheterization at Tarakan Hospital, Jakarta. A purposive sample of 32 respondents (16 intervention, 16 control) was analyzed using univariate, t-tests, and ANCOVA, with validity, reliability, homogeneity, and normality tests ensuring methodological rigor. Results: In the intervention group, the mean anxiety score dropped from 24.94 before treatment to 16.44 afterward, with statistical testing producing a p‑value of 0.000, signifying a significant impact of mindfulness. Likewise, the control group showed a reduction in average anxiety scores from 25.13 pre‑treatment to 20.88 post‑treatment, and analysis also yielded a p‑value of 0.000, indicating a significant change in anxiety levels within this group. Conclusion: Mindfulness intervention proved to be effective in reducing anxiety among patients with coronary heart disease prior to cardiac catheterization.